2018
DOI: 10.1002/stem.2913
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Human Pluripotent Stem Cells for the Modeling of Pancreatic β-Cell Pathology

Abstract: Pancreatic β‐cells are the only source of insulin. Disturbances in β‐cell development or function may thus result in insulin deficiency or excess, presenting as hyper‐ or hypoglycemia. It is increasingly evident that common forms of diabetes (types 1 and 2) are pathogenically heterogeneous. Development of efficient therapies is dependent on reliable disease models. Although animal models are remarkably useful research tools, they present limitations because of species differences. As an alternative, human plur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 91 publications
0
44
0
Order By: Relevance
“…A typical characterization pipeline to ensure pluripotency includes expression of singular pluripotency markers (SOX2 and POU5F1), karyotype analysis, and the ability to form the three germ layers using teratoma assays or embryoid body formation [1]. Despite these quality controls, numerous studies have shown major line-to-line variations [25]. To improve the utility of hPSCs in regenerative medicine and to ensure high-quality clinical-grade cell products, we need a pipeline of robust quality control methods that can be automated to benchmark the cells and filter out reprogrammed cells of inferior quality.…”
Section: Introductionmentioning
confidence: 99%
“…A typical characterization pipeline to ensure pluripotency includes expression of singular pluripotency markers (SOX2 and POU5F1), karyotype analysis, and the ability to form the three germ layers using teratoma assays or embryoid body formation [1]. Despite these quality controls, numerous studies have shown major line-to-line variations [25]. To improve the utility of hPSCs in regenerative medicine and to ensure high-quality clinical-grade cell products, we need a pipeline of robust quality control methods that can be automated to benchmark the cells and filter out reprogrammed cells of inferior quality.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies with EX-4 and resveratrol influenced this choice [41,42]. It is also important to emphasize that we look for functional insulin-secreting cells in this work rather than a pancreatic β cell phenotype, which takes in account, in addition to insulin secretion, other features such as morphology or islet aggregation (for a review, see [43]). We observed that protocols II (supplemented with EX-4 and activin A) and III (supplemented with resveratrol) generated cells with higher affinity for DTZ stain (indirect labeling of insulin presence) and pro-insulin (evaluated by Western blotting).…”
Section: Discussionmentioning
confidence: 99%
“…One successful example is the restoration of FANCA gene expression in haematopoietic stem cells ( 164 ). HDR efficiency is generally low (less than 2%) but, with CRISPR technology, it can be improved to 10-40%, depending on the target region ( 165 , 166 ). Several attempts have been made to improve HDR efficiency by incorporating silent CRISPR-Cas-blocking mutations ( 167 ), suppressing NHEJ key molecules such as KU70, KU80, or DNA ligase IV ( 168 , 169 ), modification of RAD18 ( 165 ), providing asymmetric donor DNA ( 170 ) and applying chemicals such as scr7 ( 169 ).…”
Section: Genome Editing: Tools To Explore and Correct Genetic Defectsmentioning
confidence: 99%